Interpretation:: Museum and Learning Center in Thai Society - Damrongsakul, Weeranan (FOYER: The Journal of Humanities, Social Sciences, and Education, 2025)
Access to knowledge through museums was an investigation of the roles and functions of contemporary Thai museums and learning centers in three locations: Museum Siam in Bangkok, Sirindhorn Museum in Kalasin Province, and primary schools in Uthai Thani Province.The study methods were qualitative research and action research. The data were collected from related documents, interviews, conversations, and observations. The result of the study showed that a museum is a public cultural space where visitors join in shared experiences. They can learn about history, memories, cultures, and meanings of many subjects by various interpretations. The exhibitions and a variety of activities promote creative learning in people regardless of sex or age. These experiences are promoted by museum or learning center, etc. Learning by experience brings about creativity and encourages change of members in the community. It builds knowledge, skills, attitudes, values, emotions, and beliefs and is a learning process which is individual and varies from person to person. The study also found that organizing learning activities also encourages visitors’ skills, preparing them to live in the rapid changes in Thai society.